ACTIVITY TEST OF BESTSELLING MOISTURIZERS ON SHOPEE IN TREATING SKIN PROBLEMS - Dasopang, Eva Sartika; Siahaan, Desy Natalia; Saputri, Muharni; Irnabila, Salsa (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2024)
Shopee is an e-commerce widely used by Indonesians to buy and sell products and can shop safely. Shopee shows that in 2020, moisturizers was the top selling product in the beauty category. The moisturizers sold have different ingredients, come from many brands, and have different price points. The objective of the study is to compare the 3 best-selling moisturizers in the shopee category that are more effective in improving skin problems. This study was a quantitative study using a true experimental design with a posttest only control group design consisting of 4 groups, namely 3 groups using 3 best-selling moisturizer brands based on the shopee category and 1 control group. The sample of this study was selected based on the inclusion criteria consisting of 20 volunteers and the test was conducted for 4 weeks of application on the volunteers' skin by looking at the measured parameters of moisture, pores, blemishes and wrinkles. The results showed that the activity test of moisturizer A had a faster recovery in increasing moisture content (54.8%), shrinking pore size (23.8%), reducing blemishes (19.9%) and wrinkles 28.9%.